TiO2 nanoparticles alter nutrients acquisition, growth, biomacromolecules, oil composition and modulate antioxidant defense system in Mentha arvensis L. - Subodh Kumar; Archana Dwivedi; Alok Kumar Pandey; Poornima Vajpayee (Plant Nano Biology, 2023)
The current study demonstrates the impact of TiO2 NPs (0–5 µg ml−1) on Mentha arvensis L. (Lamiaceae) cultivated commercially for essential oil. The high concentration of titanium in plant tissues (roots, leaves and stem), presence of Ti peaks in EDS of roots and accumulation of TiO2 NPs along the inner and outer membrane, cytoplasm, intracellular junctions of M. arvensis root cells after TiO2 NPs exposure reveal internalization and upward translocation of TiO2 NPs in M. arvensis. Phytotoxicity of TiO2 NPs manifested in terms of altered nutrients acquisition, reduced biomass, pigments, relative water contents and enhanced oxidative stress markers ( ≥ 2.5 µg ml−1 TiO2 NPs) in roots and leaves. Further, TiO2 NPs incremented the levels of cysteine, non-protein thiols, and proline compared to untreated control. Total phenolic contents also increased (≤1 µg ml−1 TiO2 NPs) in roots and leaves. Modulation of antioxidant enzymes (SOD, catalase, GPX, APX, AO and GST) in roots and leaves was observed to mitigate adverse effects caused by TiO2 NPs induced reactive oxygen species. TiO2 NPs differentially affects cell wall components, lipids and nucleic acids in roots and leaves. The relative peak area (%) of major oil constituents in M. arvensis leaves was significantly altered by TiO2 NPs. A concentration dependent decrement in relative peak area of α-pinene, β- pinene, Sabinene, Limonene, β – Myrcene has been documented in this study compared to unexposed plants. The present study suggests sustainable use of TiO2 NPs in agriculture and other commercial products due to their potential biotoxicity.